Economic risk assessment of infrastructure systems due to earthquakes - Lim, Jasmine Yi Jin. (2012)
Earthquakes are unpredictable and catastrophic, often inflicting significant damages and resulting in high casualties. The past ten years have seen a sharp rise in the rate of earthquakes occurring, in particular those which have had devastating consequences. For example, the 2004 Indian Ocean Earthquake, the 2008 Sichuan Earthquake, the 2010 Haiti Earthquake, the 2010 Chile Earthquake and the 2011 Tohoku Earthquake. Hence, there is a growing impetus to develop accurate and detailed risk assessment of earthquakes.This report shall explain the natural phenomenon of earthquake. A brief comparison of the notable recent major earthquakes, such as the 2010 Haiti Earthquake, the 2010 Chile Earthquake and the 2011 Tohoku Earthquake, shall follow. Subsequently, the report elaborates on the Earthquake Risk Assessment Approach – hazard analysis, inventory collection, damage modelling, and loss estimation [Opus International Consultants Limited, August 2005]. Finally on the basis of the above, an economic earthquake risk assessment for the city of Seattle in King County, Washington, USA concludes the report. Where possible, diagrams, tables and raw data are used to illustrate and elaborate on the analysis in the report.